2012
DOI: 10.1093/rpd/ncs147
|View full text |Cite
|
Sign up to set email alerts
|

Canadian population risk of radon induced lung cancer: a re-assessment based on the recent cross-Canada radon survey

Abstract: Exposure to indoor radon has been determined to be the second leading cause of lung cancer after tobacco smoking. Canadian population risk of radon induced lung cancer was assessed in 2005 with the radon distribution characteristics determined from a radon survey carried out in the late 1970s in 19 cities. In that survey, a grab sampling method was used to measure radon levels. The observed radon concentration in 14 000 Canadian homes surveyed followed a log–normal distribution with a geometric mean (GM) of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 3 publications
(6 reference statements)
7
47
2
Order By: Relevance
“…8 However, although the mean radon level for Canada (41.9 Bq/m 3 ) calculated with more recent data 8 is closer to that observed for Alberta in the current study (71.0 Bq/m 3 ), overall radon levels in Alberta were still higher than comparable values at the national level. Differences in the model used to estimate population attributable risk by Chen and colleagues 8 and in our study likely explain why the estimates of population attributable risk are similar despite higher levels of radon exposure in Alberta.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…8 However, although the mean radon level for Canada (41.9 Bq/m 3 ) calculated with more recent data 8 is closer to that observed for Alberta in the current study (71.0 Bq/m 3 ), overall radon levels in Alberta were still higher than comparable values at the national level. Differences in the model used to estimate population attributable risk by Chen and colleagues 8 and in our study likely explain why the estimates of population attributable risk are similar despite higher levels of radon exposure in Alberta.…”
Section: Discussionsupporting
confidence: 70%
“…She found that the estimated population attributable risks were a bit higher than those observed by Brand and colleagues 6 (ever smokers 7.3%, never smokers 13.5%). More recently, Chen and colleagues 8 applied the Environmental Protection Agency method to data from the CCSRCH and observed a geometric mean radon level of 41.9 Bq/m 3 , which translated to an estimated population attributable risk of about 16%, virtually the same as our estimate. Outside Canada, Gray and colleagues 19 estimated that with a mean indoor radon concentration of 21 Bq/m 3 , the proportion of lung cancer deaths attributable to radon exposure in the United Kingdom in 2006 was 3.3%.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The observed radon concentrations in Canadian homes follow a log-normal distribution (Chen et al 2012). This was also true for the Arctic health regions.…”
Section: Resultsmentioning
confidence: 95%
“…Long-term radon measurements were performed in all the homes surveyed. The observed radon concentrations in Canadian homes follow a log-normal distribution (Chen et al 2012). Because of the wide distribution in radon concentrations, a central estimate alone, such as arithmetic mean (AM) or geometric mean (GM), will not be able to represent the distribution.…”
Section: Methodsmentioning
confidence: 99%